2021
DOI: 10.1108/acmm-03-2020-2286
|View full text |Cite
|
Sign up to set email alerts
|

Study on hydrogen permeation behavior of X80 steel under AC stray current interference

Abstract: Purpose Alternating current (AC) corrosion is a type of corrosion that occurs in buried pipelines under AC stray current interference, which can increase the hydrogen embrittlement sensitivity of pipelines. However, rare research works have been conducted on the hydrogen permeability characteristics of pipeline steel under AC stray current interference. The purpose of this paper is to study hydrogen permeation behavior of X80 steel under AC stray current interference. Design/methodology/approach In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…It is evident that the main reason for this type of corrosion is the existence of AC. The result is consistent with the report of Wang et al (2021) that under the combined effects of hydrogen and stress, SCC behavior occurs in metals.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…It is evident that the main reason for this type of corrosion is the existence of AC. The result is consistent with the report of Wang et al (2021) that under the combined effects of hydrogen and stress, SCC behavior occurs in metals.…”
Section: Resultssupporting
confidence: 93%
“…From Figure 10, we can see that the corrosion rate was changed with the CP potential. Figure 10 also confirms the findings of Wang et al that with the decreasing electrode potential, the corrosion degree of the sample first decreases and then increases, and the SCC sensitivity exhibits a certain rule (Wang et al , 2021).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…There are intricate interactions between microorganisms, and the biofilm and corrosion products generated by metabolic processes can promote or hinder the corrosion process (Li et al , 2013; Lv et al , 2022; Liu et al , 2022). In addition, under the condition of hydrogen-mixed transportation, hydrogen atoms will inevitably penetrate into the pipes, which easily causes corrosion fatigue, stress corrosion, hydrogen embrittlement and other phenomena (Wang et al , 2021). Meiring (Lv et al , 2021) studied the effect of SRB on hydrogen permeation and stress corrosion cracking behavior of high-strength steel in the seawater environment and found that SRB would raise the risk of stress corrosion cracking of high-strength steel.…”
Section: Introductionmentioning
confidence: 99%